Limitaç\~oes de um teste de meios via prediç\~ao de renda: Evidências de uma aplicaç\~ao no Programa Bolsa Família - Joana Mostafa; Thuany dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The impact of Programa Bolsa Família in reducing extreme poverty has its roots on the program's precision as well as coverage. Its results are only hindered by the modest values transferred, totaling only 0,5% of the Brazilian GDP in the hands of the poorest quartile. Notwithstanding the national and international evidence of the Program's success, the specter of bad targeting reappeared as the political crisis of Dilma Rousseff's government thrived. Nothing further from reality. Programa Bolsa Família is a rare example in Brazilian public policy of constant auditing and benefit revision. Additionally, its responsible managers have applied a proxy means test methodology in the context of the 2013 audit, shedding more light on the determinants of poverty in Brazil and revealing serious limitations of these instruments, be it to determine eligibility or revise benefits so essential to these families' survival. These findings are registered in this discussion paper.
Keywords: I3; 330; Bolsa Família; targeting; means test; proxy means test